2015
DOI: 10.1186/s40560-015-0108-1
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of the association between microalbuminuria and increased N-terminal pro-B-type natriuretic peptide in patients with subarachnoid hemorrhage

Abstract: BackgroundThe urinary albumin/creatinine ratio (ACR) is a significant neurologic prognostic predictor in patients with aneurysmal subarachnoid hemorrhage (SAH). B-type natriuretic peptide (BNP) plays an important role in body fluid regulation in patients with SAH. The present study was performed to determine whether ACR was independent predictor for unfavorable neurological outcome and ACR was associated with increased N-terminal pro-BNP (NT-pro-BNP) after SAH.MethodsWe studied 61 patients undergoing surgery w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The NT-proBNP has been previously considered as a predictive biomarker for diagnosis and prognosis of patients with cardiovascular disease, such as left ventricular dysfunction, systolic and diastolic dysfunction, and acute coronary syndromes. [13][14][15] Recently, some studies showed that elevation in NT-proBNP was common in patients hospitalized with ischemic stroke, SAH, and ICH, as well as TBI, [3][4][5][6][7][8][9]16 suggesting that NT-proBNP might play a role after acute brain injury. However, the change pattern of NT-proBNP after isolated HICH was barely reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NT-proBNP has been previously considered as a predictive biomarker for diagnosis and prognosis of patients with cardiovascular disease, such as left ventricular dysfunction, systolic and diastolic dysfunction, and acute coronary syndromes. [13][14][15] Recently, some studies showed that elevation in NT-proBNP was common in patients hospitalized with ischemic stroke, SAH, and ICH, as well as TBI, [3][4][5][6][7][8][9]16 suggesting that NT-proBNP might play a role after acute brain injury. However, the change pattern of NT-proBNP after isolated HICH was barely reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that the levels of serum BNP or N-terminal pro-BNP (NT-proBNP), a circulating precursor of BNP, increased during the acute phase of cerebral lesions such as traumatic brain injury (TBI), 3 ischemic stroke, [4][5][6] and subarachnoid hemorrhage (SAH). [7][8][9] The increased plasma BNP levels might be the main cause of cerebral salt wasting syndrome, which is characterized by hyponatremia and natriuresis after SAH. 7 However, the role of NT-proBNP in HICH is poorly understood, and the relationship between NT-proBNP and hyponatremia, which could lead to malignant brain edema and elevation in intracranial pressure (ICP), is still a controversial issue.…”
Section: Introductionmentioning
confidence: 99%
“… 70 The UACR is also a significant neurologic prognostic predictor in patients with aneurysmal subarachnoid hemorrhage; the mechanism of association between the 2 disorders is not known. 71 Microalbuminuria is also a prognostic marker of cardiopulmonary complications after major surgery. However, its independent prognostic significance remains to be established.…”
Section: Association Of Albuminuria With Cardiovascular Diseasementioning
confidence: 99%